2021
DOI: 10.1111/opn.12369
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric comparisons of measures of eHealth literacy using a sample of Korean older adults

Abstract: Aims: This study aimed to compare the psychometric properties of two measures of eHealth literacy, namely, the Korean versions of the Digital Health Literacy Instrument (K-DHLI) and eHealth Literacy Scale (K-eHEALS), among older adults in South Korea. Background:Given the usefulness of eHealth information, measures of eHealth literacy have been developed. It is necessary to examine the validity of such tools among older adults who are likely to experience difficulties in using eHealth resources.Methods: A vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
7
18
0
Order By: Relevance
“…The characteristics of the included eHealth literacy instruments and studies are presented in Multimedia Appendix 2 [ 24 - 64 ]. The eHEALS, which consists of 8 items scored on a 5-point Likert scale, was originally developed in English [ 24 ], and its psychometrics have been studied in diverse languages: Amharic [ 50 ], Mandarin Chinese [ 26 ], Simplified Chinese [ 34 , 36 , 41 ], Dutch [ 25 ], English [ 27 - 30 , 47 , 53 , 54 , 57 , 58 ], German [ 39 , 44 ], Greek [ 48 ], Hebrew [ 45 ], Hungarian [ 37 ], Indonesian [ 43 ], Italian [ 31 , 33 ], Korean [ 32 , 42 , 55 ], Persian [ 38 , 46 ], Polish [ 35 ], Portuguese [ 52 ], Norwegian [ 49 , 56 ], Serbian [ 51 ], and Swedish [ 40 ]. The eHEALS has been used to evaluate diverse populations, including not only youths, adults, and older adults, but also healthy people, patients, caregivers, and health professionals in school, community, and clinic settings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the included eHealth literacy instruments and studies are presented in Multimedia Appendix 2 [ 24 - 64 ]. The eHEALS, which consists of 8 items scored on a 5-point Likert scale, was originally developed in English [ 24 ], and its psychometrics have been studied in diverse languages: Amharic [ 50 ], Mandarin Chinese [ 26 ], Simplified Chinese [ 34 , 36 , 41 ], Dutch [ 25 ], English [ 27 - 30 , 47 , 53 , 54 , 57 , 58 ], German [ 39 , 44 ], Greek [ 48 ], Hebrew [ 45 ], Hungarian [ 37 ], Indonesian [ 43 ], Italian [ 31 , 33 ], Korean [ 32 , 42 , 55 ], Persian [ 38 , 46 ], Polish [ 35 ], Portuguese [ 52 ], Norwegian [ 49 , 56 ], Serbian [ 51 ], and Swedish [ 40 ]. The eHEALS has been used to evaluate diverse populations, including not only youths, adults, and older adults, but also healthy people, patients, caregivers, and health professionals in school, community, and clinic settings.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this instrument has 3 items that are not obligatory to answer when respondents do not have experience posting messages on social media (ie, they can leave the items blank). The DHLI was further assessed in the Korean language for older adults in welfare centers [ 42 ]. The eHLA is the longest instrument, comprising 42 items scored on a 4-point Likert scale and using multiple choices, and was developed in both Danish and English [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new tool DHLI can include interactivities on the web, so-called “e-Health 2.0 Skills” [ 15 ]. The Korean version of the eHealth Literacy Scale (K-eHEALS) was validated among young adults [ 16 ] and among older adults [ 17 , 18 ]. Among older people, the validated K-DHLI, composed of 21 items with five factors, was recently introduced [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Korean version of the eHealth Literacy Scale (K-eHEALS) was validated among young adults [ 16 ] and among older adults [ 17 , 18 ]. Among older people, the validated K-DHLI, composed of 21 items with five factors, was recently introduced [ 18 ]. Previous studies reported an association between digital health literacy and doctor–patient communication [ 19 ], as well as preventive health behaviors [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%